BUILDING SCHOOL AND FAMILY PARTNERSHIPS TO PREVENT BULLYING IN CHILDREN - Astutik, Kurniah; Destiani, Lita Putri; Hasanah, Putri Huswatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The background to this research is that bullying is increasing in the school environment. Efforts that schools can make to prevent bullying among students are by building partnerships with families as the main scope of education that students receive outside of school. Because the first education in forming a strong character and good spirit starts from the family environment. The partnership process between schools and families is a key factor in school success in various aspects. So, it is very important that the family environment and the school environment can work together to build partnerships in efforts to prevent bullying in children. The general aim of this research is to provide qualitative descriptive information for teaching and educational staff in schools regarding the importance of building partnerships with families to prevent bullying in children. The research method used is descriptive qualitative through observation, interviews and documentation with class teachers and parents and guardians systematically and factually based on reality in the field. The data analysis techniques used are: 1) Deductive, namely analyzing data from general matters to specific matters, then drawing a conclusion; 2) Inductive, namely analyzing data from specific matters with general matters, then drawing conclusions, and 3) Comparative, namely analyzing data by comparing data obtained through library research as theory with data from research results and interviews. regarding the school's partnership with families which then forms an effort to prevent and control bullying in schools. The results of this research in general are; 1) Implementation of partnerships with families in efforts to prevent and overcome bullying at SDN Kotakulon 1, 2) Evaluation of the implementation of school partnerships with families in efforts to prevent and overcome bullying at SDN Kotakulon 1, 3) Forms of school assistance for victims of bullying at SDN Kotakulon 1.